Nutritional status and associated factors among elderly people in Cameroon - (:unkn) unknown (My University, 2021)
The ageing of the Cameroonian population seems to be increasing, and the nutritional status of the elderly is not known. The main objective of this thesis was to assess the nutritional status of the elderly in Cameroon, as well as the factors associated with nutritional disorders. A nationally representative cross-sectional study was conducted among 599 persons aged 60 years and above (sex ratio M/F: 0.93). Socio-demographic, health, anthropometric, functional and neuropsychological data were collected. The prevalence of undernutrition was 19.7%, negatively associated with the absence of treatment, and that of obesity was 17.5%, positively associated with urban environment and inactivity, and negatively associated with male gender, widowhood, position as head of household, lack of income, presence of a pathology, absence of treatment and normal diastolic pressure. In 24.9% of the cases there was a limitation in mobility, in 22.2% or 48.2% of the cases there were limitations in the activities of daily living (according to the ADL or IADL scale respectively), in 14.5% of the cases there was a depressive syndrome and 21.4% of the persons had cognitive disorders, mostly positively associated with advanced age, inactivity, obesity and lack of income. A systematic review of the nutritional status of the elderly in Africa was carried out in parallel with the Cameroonian study, as well as a study of residents in EHPAD in France. All the studies highlighted that undernutrition affects 20 to 30% of the elderly and suggested that the problems of overweight elderly people will have an increasing impact on the health of African populations in the future. This might justify the rapid adoption of preventive measures.
Keywords: African Research